Enhancing Redundancy in Wireless Visual Sensor Networks for Target Coverage - Costa, Daniel G.; Silva, Ivanovitch M. D.; Guedes, Luiz Affonso; Portugal, Paulo; Vasques, Francisco (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2014: Proceedings of the 20th Brazilian Symposium on Multimedia and the Web, 2014)
Wireless visual sensor networks provide valuable information for many monitoring and control applications. Sometimes, a set of targets needs to be monitored by deployed visual sensors. For those networks, however, some active visual sources may fail, potentially degrading the application monitoring quality when targets become uncovered. Moreover, some applications may need different perspectives of the same target. As visual sensors will be used to monitor a set of targets, a high level of monitoring redundancy may be required and an effective way to achieve it is assuring that targets are being concurrently viewed by more than one visual sensor. We propose a centralized greedy algorithm to enhance redundancy in wireless visual sensor networks when visual sensors with adjustable orientations are deployed. Additionally, as some targets may be more critical for the application, we propose a priority-based configuration of the sensors' poses in order to achieve an optimized configuration for the visual sensors.